2015
DOI: 10.1002/ceat.201500093
|View full text |Cite
|
Sign up to set email alerts
|

Design and Numerical Simulation Analysis of an Integrative Gas‐Liquid‐Solid Separation Hydrocyclone

Abstract: Normally, a gas-liquid-solid separation includes both degassing and desanding processes, which means a relatively higher facility investment and larger energy consumption. Based on an inner-cone hydrocyclone developed before, an integrative degassing and desanding hydrocyclone was designed. Its design idea and process are described in detail. By means of a hollow inner cone (IC), the separated liquid enters into the cone through holes on it and then flows to the liquidphase outlet. Due to integrative separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hydrocyclones have been broadly implemented in various industries due to several advantages, such as their simple geometrical structure, low operating costs, small footprint, easy maintenance, and high separation efficiency 1–4. Industrial applications of hydrocyclones include mineral extraction 5, chemical engineering 6, 7, coal and petroleum extraction and refinement 8, 9, pulp processes 10, environmental protection and waste management 11, 12, agriculture and aquaculture 13, 14, food processing 15, biotechnology 16, material science and nanotechnology 17, 18, and thermal energy recovery 19.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocyclones have been broadly implemented in various industries due to several advantages, such as their simple geometrical structure, low operating costs, small footprint, easy maintenance, and high separation efficiency 1–4. Industrial applications of hydrocyclones include mineral extraction 5, chemical engineering 6, 7, coal and petroleum extraction and refinement 8, 9, pulp processes 10, environmental protection and waste management 11, 12, agriculture and aquaculture 13, 14, food processing 15, biotechnology 16, material science and nanotechnology 17, 18, and thermal energy recovery 19.…”
Section: Introductionmentioning
confidence: 99%
“…There are two basic types of passive degassing cyclones, i.e., swirl vane separators which swirling flow results from guide vanes [8] and cyclonic separators which is an evolution from hydrocyclone mounted with a tangential inlet, with two outlets provided at the top and the bottom. The examples of cyclonic separators include gas-liquid cylindrical cyclone separator (GLCC) [9], inner-cone hydrocyclone [10,11], bubble eliminator with two tangential inlets [12], and planar cyclone for bubble separation [13]. According to an experimental report about planar degassing cyclones [13], only 0.075-0.323 s is needed to separate 100-μm bubbles with a cyclone diameter of 50 mm and tangential inlet velocity ranging from 3.7 to 7.4 m s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Processes 2020, 8, 1617 2 of 11 Zhao et al [1] and Bogodage et al [2] used single particle dynamics model to numerically calculate the moving track and separation efficiency of water droplets in the corrugated plate and pointed out that the deflection angle of the corrugated plates should not be greater than 45 • . Li et al [3] calculated droplet trajectory phenomenon and separation efficiency and found that the droplets flow velocities at different inlets corresponded to a critical particle size and the critical value decreased with the increase of the inlet droplets velocity.…”
Section: Introductionmentioning
confidence: 99%